The Oral Tradition of Hoyak Tabuik in Pariaman, West Sumatera: An Anthropolinguistic Approach - Akmal; Lubis, Tasnim (Tradition and Modernity of Humanity, 2022)
Hoyak tabuik deals with a religious and old tradition from Minangkabau. It passed from the ancerstor to the next generation. It is one of the local wisdom still used in the Pariaman society to recall the Hasan-Hussein death. This study used qualitative research and anthropolinguistic approach. The data were literature from books and interview the Pariamaneses. There are a lot of oral traditions could be taken from the tabuik ceremony, including that all the worst traits should be removed from our lives, and it can be seen that they throw tabuik constructions into the sea. from the result of the study, it can be observed that Hoyak tabuik still do by the community regarding the figures of Hasan and Husen who was killed by their enemy. The symbols in Hoyak tabuik indexed the incident of the chronology of Hasan Husen death.